Microwave-assisted Production and Vacuum Distillation for Improved Cold-Flow Properties of Palm Fatty Acid Distillate (PFAD) Biodiesel - Yeong, Siew Ping (Curtin University, 2020)
This study aims to produce biodiesel with improved cold flow properties from PFAD feedstock by utilizing microwave and vacuum distillation technologies. Microwave-assisted PFAD esterification reaction is modelled by a novel three-dimensional multiphysics model which incorporates electromagnetic wave, heat transfer, fluid flow and the 2nd order esterification reactions. The ester compositions of PFAD biodiesel can be modified via vacuum fractional distillation to produce export grade biodiesel for temperate climates.